Serie escultórica de las costumbres en las familias del cantón Zaruma en el año 2012. - Valarezo Blacio, Ángel Bladimir (2013)
The result of the interviews with historians and illustrious people of the city and its parishes have even members of my family Uncles, are reflected familiar images as well as their work and production that is part of their culture, which define their cultural difference Ecuador to the zarumeño.